Thermal exposure conditions for a composite liner with a black geomembrane exposed to solar radiation. Issue 1 (1st February 2015) - Brachman, R.W.I.; Rowe, R.K.; Arnepalli, D.N.; Take, W.A.
Abstract : ABSTRACT: A black 1.5 mm geomembrane (GMB) and geosynthetic clay liner (GCL) liner were placed on both a 3H: 1V (18.4°) slope and a gently sloping (3%) base (latitude 44°34′15″N) and left exposed for 4.7 years. The observed solar radiation, ambient air temperature, temperature at the interface between the GMB and GCL, and temperature at various depths (to 600 mm) in the underlying silty sand soil are reported. The interface temperature was up to 40°C higher than ambient temperature on a sunny day. The difference between interface temperature on the slope and base was minimal near summer solstice and increased significantly earlier and later in the year (except when covered in snow). There was significant variability in GMB and interface temperature depending on the contact conditions between the GMB and GCL. The interface temperatures at wrinkles could be 15°C higher than other locations where there was intimate contact between GMB and GCL. Snow-cover insulated the liner from solar radiation and extreme temperature. These insulating effects were lost on the south-facing slope before the base, subjecting the GCL on the slope to more daily freeze–thaw cycles than on the base. A correlation between the interface temperature, ambient air temperature, and the solar radiation gave good agreement with the observed temperatures. The cycling of interface temperatures is considered to be central to the mechanism of moisture evaporation from the GCL that may cause GCL panel shrinkage and moisture condensation-driven downslope bentonite erosion. Covering the composite liner with a ballast layer as quickly as possible is recommended.